The Effectiveness of Mobile Learning Teaching Materials for Education on Sustainable Development in Eco-Friendly Technology to Improve Environmental Literacy - Layyinah, Syifa Qalbiyatul; Sinaga, Parlindungan; Amprasto, Amprasto (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study aimed to develop mobile learning teaching materials based on Education for Sustainable Development (ESD) with a focus on Eco-Friendly Technology and to test their effectiveness in improving Environmental Literacy. The teaching materials were developed using the ADDIE model. A total of 58 9th-grade students participated in the study, divided into an experimental group and a control group. The instruments used included an Environmental Literacy test and assessment tools to evaluate the quality of the teaching materials and comprehension test sheets. The data were analyzed by calculating the average normalized gain, conducting t-tests for means, and measuring the effect size. The analysis revealed the following results: 1) The quality test and reading comprehension test scores were good; 2) The Environmental Literacy skills of the experimental group showed a medium increase, while the control group showed a low increase; 3) There was a significant difference in the increased Environmental Literacy skills between the experimental and control groups, indicating that the teaching materials were effective in improving Environmental Literacy skills, with an N-Gain of 0.41, which falls into the medium category; and 4) The effect size test yielded a score of 1.2, categorizing it as high, which means that the teaching materials were effective in enhancing students’ environmental literacy skills.